Halogenated Sodium-closo-Dodecaboranes as Solid-State Ion Conductors - Hansen, B.; Paskevicius, Mark; Jørgensen, M.; Jensen, T. (American Chemical Society, 2017)
Sodium compounds containing large weakly coordinating anions are explored as ion conductors. The halogenated sodium-closo-dodecaboranes (Na2B12Cl12, Na2B12Br12, and Na2B12I12) are all isostructural (Pa3¯) at room temperature. These compounds undergo an order-disorder polymorphic transition to Fm3¯m where Na+ partially occupies two crystallographic sites and [B12X12]2- anions undergo reorientational motion. These dynamic structural properties promote extreme Na+ ion conductivity up to 0.162 S/cm at elevated temperature (500 °C). The polymorphic transition temperatures increase down the halogen group (Cl < Br < I). These temperatures are much higher (475, 525, and 570 °C) than for Na2B12H12 (266 °C), which could be related to increasing anion size, mass, and the anisotropic electron density in the covalently bound halogens (B-X). The halogens may form Na-X interactions with increasing strength and directionality, which restrict dynamic motion until high temperature. The halogenated sodium-closo-dodecaboranes demonstrate excellent thermal stabilities (up to 500 °C) and may facilitate the development of new high temperature ion conductors.